2020
DOI: 10.1007/s10290-020-00398-8
|View full text |Cite
|
Sign up to set email alerts
|

Global value chains and technology transfer: new evidence from developing countries

Abstract: International trade has long been considered a channel of technology transfer. This paper draws from the World Bank’s Enterprise Surveys to provide a sample of 18 developing and emerging economies to investigate whether global value chains (GVCs) are a vehicle for the transfer of technology. It focuses on one specific channel for technology transfer, namely, the licensing of foreign technology. To control for the possible endogeneity of technology licensing, propensity score matching is combined with a differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 52 publications
0
15
1
3
Order By: Relevance
“…On the contrary, independent R&D activities of leading local enterprises will be fully suppressed by multinational enterprises and lose more profit distribution in the short term. This finding is quite different from the previous that foreign technology spillovers in the global value chain system can help local enterprises increase their productivity (Rigo, 2020). Second, we found that the R&D activities of small and medium‐sized local enterprises can help reduce the degree of suppression of leading local enterprises by multinational enterprises.…”
Section: Conclusion and Managerial Insightscontrasting
confidence: 98%
See 1 more Smart Citation
“…On the contrary, independent R&D activities of leading local enterprises will be fully suppressed by multinational enterprises and lose more profit distribution in the short term. This finding is quite different from the previous that foreign technology spillovers in the global value chain system can help local enterprises increase their productivity (Rigo, 2020). Second, we found that the R&D activities of small and medium‐sized local enterprises can help reduce the degree of suppression of leading local enterprises by multinational enterprises.…”
Section: Conclusion and Managerial Insightscontrasting
confidence: 98%
“…Kimseng et al (2020) argued that the knowledge exchange in the global value chain system can help enterprises to carry out innovative activities. Rigo (2020) believed that foreign technology spillovers in the global value chain system can help local enterprises to increase their productivity. Hao et al (2021) explored the impact of international technology spillovers on the carbon emissions of local Chinese companies and found that the impact of technology spillover on carbon emissions is different in central and western China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following Baldwin and Yan (2014), Del Prete et al (2017), and Rigo (2021, GVC firms are identified using a binary variable that takes the value 1 if the firm is simultaneously importing intermediates (raw materials, stores and spares, and capital goods and services) and exporting at a given point of time. 3 Non-GVC firms are either those that conduct one-way trade (import or export) or those that are not internationalized, that is, they conduct little or no international trade and serve only the domestic market.…”
Section: Identifying Gvc Status and Gvc Embeddedness Of Indian Manufa...mentioning
confidence: 99%
“…The participation in Global Value Chain (GVC) can significantly contribute to productivity improvement, economic growth, job creation and poverty reduction (Rigo 2021;World Bank 2020). An increase of participation in GVC could also reduce the competitiveness gap between small and large firms (Boffa et al 2021).…”
Section: Markets and Value Chainsmentioning
confidence: 99%
“…The work can be distinguished from other efforts related to food and agriculture (e.g. ISDC's 2018 volume edited by Serraj and Pingali, FAO's annual State of Food and Agriculture report (FAO 2020;2021;, IFAD's periodic Rural Development Report (IFAD 2016;2021), OECD-FAO's annual Agricultural Outlook report (OECD and FAO 2020;2021), the World Bank's World Development Report (World Bank 2008;2010;2021), and others) in terms of time horizon, geographic or thematic focus. The work adds to other foresight analyses, e.g.…”
Section: Introductionmentioning
confidence: 99%